Development of a Molecular Serotyping Scheme for Morganella morganii - Liu, Bin; Guo, Xi; Wang, Jing; Wu, Pan; Li, Shujie; Feng, Lu; Liu, Bin; Wang, Lei (Frontiers in Microbiology, 2021)
Morganella morganii, which is often regarded as a human commensal organism, can be an opportunistic pathogen, causing a variety of clinical infections with serious morbidity and mortality. An efficient and convenient method for subtyping and identifying M. morganii strains in epidemiological surveillance and control is urgently needed. Serotyping based on bacterial surface polysaccharide antigens (O-antigen or K-antigens) is a standard subtyping method for many gram-negative bacteria. Here, through whole genome sequencing and comparative genomics analysis of 27 strains, we developed a molecular serotyping scheme based on the genetic variation of O-antigen gene clusters (O-AGC) in M. morganii, and 11 distinct O-AGC types were identified. A conventional serotyping scheme was also developed by the production of antisera and agglutination experiments, which was shown to be perfectly consistent with the molecular serotyping scheme, confirming that the variation in M. morganii O-AGC correlated with phenotypic O-antigen diversification. Furthermore, a microsphere-based suspension array (MSA) with high specificity was developed based on the specific genes within each O-AGC type. The sensitivity of MSA was determined to be 0.1 ng of genomic DNA and 103 CFU of pure culture. We further analyzed 104 M. morganii genomes available in GenBank, and an additional six novel O-AGC types were identified, indicating that the extension of this molecular serotyping scheme is convenient. Our work provides an important tool for the detection and epidemiological surveillance of M. morganii, and this method has the potential to be widely utilized, especially for bacterial genera/species without an efficient typing approach.